PRAKTIK MONEY POLITIC DALAM PEMILIHAN ANGGOTA LEGISLATIF KOTA SURAKARTA DAN PENGARUHNYA TERHADAP TINGKAT PARTISIPASI PEMILIH DI WILAYAH KELURAHAN MOJOSONGO, JEBRES, SURAKARTA TAHUN 2019: PRAKTIK MONEY POLITIC DALAM PEMILIHAN ANGGOTA LEGISLATIF KOTA SURAKARTA DAN PENGARUHNYA TERHADAP TINGKAT PARTISIPASI PEMILIH DI WILAYAH KELURAHAN MOJOSONGO, JEBRES, SURAKARTA TAHUN 2019 - Prabowo Jhoni; Sutoyo Sutoyo; Sugiaryo Sugiaryo (Prodi PPkn Universitas Slamet Riyadi, 2023)
ABSTRACT The purpose of this research is to: (1) reveal whether it is true that money politics has occurred in the election of members of the Surakarta city legislature, especially in the Mojosongo Village area, Jebres, Surakarta in 2019; (2) Knowing the forms of money politics practices that occurred in the election of members of the Surakarta City legislature, especially in the Mojosongo Village area, Jebres, Surakarta in 2019; (3) Knowing the effect of the practice of money politics in the election of members of the Surakarta City legislature, especially in the Mojosongo Village area, Jebres, Surakarta in 2019 on the level of voter participation. This research was carried out in the Mojosongo Village Area, Jebres District, Surakarta City. The subjects of this study included the voting community, the chairperson or member of the winning team for legislative member candidates, and village officials in the Mojosongo Village area, Jebres, Surakarta. Sources of data using primary data sources and secondary data sources. Data collection in this study was carried out through interviews, documentation, and observation. Test the validity of the data using source triangulation and technique triangulation. The data in this study were analyzed using interactive model descriptive analysis techniques. The results of the study can be concluded that: (1) The election for legislative members in 2019, especially in the Mojosongo sub-district area, Jebres sub-district, Surakarta city, justifies the practice of money politics, which was carried out by prospective members of the Surakarta city legislature through their winning team; (2) The form of money politics given in the 2019 election for legislative members in the city of Surakarta, especially in the Mojosongo sub-district area, includes giving cash to the community, repairing existing infrastructure in the village, and providing facilities and infrastructure in the village for the benefit of the community. There is; (3) The practice of money politics in the election for members of the Surakarta City legislature in 2019, especially in the Mojosongo sub-district area, had an influence on the turnout rate of voters who were present at the polling stations, because based on the results of interviews it was found that the number of voters in the Mojosongo Sub-district area had increased. Keywords: Legislative Members, Voter Participation, Money Politics.